Spatial stimuli in films: Uncovering the relationship between cognitive emotion and perceived environmental quality - Sakhaei, Hamidreza; Biloria, Nimish; Azizmohammad Looha, Mehdi (Frontiers in Psychology, 2022)
Objectives The research paper establishes the impact of spatial stimulus on human cognition and emotion by studying environmental events as cues to understand how people perceive spatial qualities. The medium of film to implement visually disruptive events was used in the research to find the relationship between the subjective evaluation of space and emotional responses. Method Ninety participants participated in watching three films showcasing unexpected spatial stimuli, thus impacting their psychological state. Standard questionnaires involving Aesthetic chills and The Self-Assessment Manikin (SAM) model were used to capture emotional responses, and Normalized Accumulated Quality (NAQ) model was used to receive space quality assessments. The Pearson correlation coefficient was subsequently used to find the association of chills and The SAM with NAQ. Univariate and multivariate regression models were also conducted to find the impact of emotional responses on NAQ. Results A significant association of NAQ with chills (p-value: 0.001), pleasure (p-value <0.001), arousal (p-value: 0.016), and dominance (p-value: 0.015) was witnessed in film 1. In film 2, NAQ was significantly associated with pleasure (p-value <0.001), while in film 3, NAQ was highly associated with arousal (p-value: 0.043). According to the adjusted impact of variables on NAQ in film 1, significant impacts of chills (p-value: 0.028), arousal (p-value: 0.117), pleasure (p-value <0.001), and dominance (p-value: 0.113) on NAQ were observed. In film 2, pleasure (p-value <0.001) and dominance (p-value: 0.113) impacted NAQ using the univariate model, while only pleasure had an impact on NAQ in the multivariate model. In film 3, arousal was the only variable to impact NAQ (p-value: 0.043) in a univariate model. In regression analyses, higher slopes were witnessed for models in film 1. Conclusion The experiment highlighted that using affect-based video clips can help us capture the relationship between emotional responses and perceived quality of space. The appearance of spatial stimuli can engage learning, expectation, and attention, leading to a superior improvement of cognitive ability and mental health in space. This level of understanding can help design a more sustainable place.